Studi Kasus Teknik Radiografi Vertebrae Lumbal Dengan Klinis Lumbal Spinal Stenosis - nana, nana andriana juniati (Sahabat Publikasi Kuu, 2024)
Radiographic examination of the lumbar spine in clinical lumbar spinal stenosis according to Lampignano (2018) uses AP and lateral projections. According to Yurube (2017) AP, lateral and oblique, and according to Mawansa (2018) PA prone, while radiographic examination of the lumbar vertebrae in cases of lumbar spinal stenosis at Prof. Orthopedic Hospital. Dr. R. Soeharso Surakarta uses 4 projections namely AP, lateral, lateral flexion and lateral extension with the patient standing or erect. This study aims to determine the technique of radiographic examination of the lumbar vertebrae in cases of lumbar spinal stenosis and the reasons for using additional lateral flexion and lateral extension projections. This type of research is qualitative with a case study approach. The research was conducted at the Radiology Installation of RSO Surakarta in September 2022- May 2023. Data was collected by observation, documentation and interviews with 3 radiographers and 1 radiologist. Then the data is presented to draw conclusions. The results of the study were examination of the lumbar vertebrae in cases of lumbar spinal stenosis at the Radiology Installation of RSO Surakarta, which was carried out using AP, lateral, lateral flexion and lateral extension projections. The rationale for using additional lateral flexion and lateral extension projections on lumbar examination is to show any narrowing of the intervertebral discs, reveal osteophytes, listhesis and tumors in the lumbar region, and provide additional information on lumbar stability. It is advisable to examine the lumbar vertebrae with clinical lumbar spinal stenosis using 4 AP projections, lateral, lateral flexion and lateral because these projections can show narrowing of the intervertebral disc and can also provide a good clinical diagnosis of lumbar spinal stenosis.